Informing primary care reform in Greece: patient expectations and experiences (the QUALICOPC study) - Lionis, Christos; Papadakis, Sophia; Tatsi, Chrysanthi; Bertsias, Antonis; Duijker, George; Mekouris, Prodromos-Bodosakis; Boerma, Wienke; Schäfer, Willemijn (Université d'Ottawa | University of Ottawa, 2017)
Abstract Background Primary health care is the cornerstone of a high quality health care system. Greece has been actively attempting to reform health care services in order to improve heath outcomes and reduce health care spending. Patient-centered approaches to health care delivery have been increasingly acknowledged for their value informing quality improvement activities. This paper reports the quality of primary health care services in Greece as perceived by patients and aspects of health care delivery that are valued by patients. Methods This study was conducted as part of the Quality and Costs of Primary Care in Europe (QUALICOPC) study. A cross-sectional sample of patients were recruited from general practitioner’s offices in Greece and surveyed. Patients rated five features of person-focused primary care: accessibility; continuity and coordination; comprehensiveness; patient activation; and doctor–patient communication. One tenth of the patients ranked the importance of each feature on a scale of one to four, and nine tenths of patients scored their experiences of care received. Comparisons were made between patients with and without chronic disease. Results The sample included 220 general practitioners from both public and private sector. A total of 1964 patients that completed the experience questionnaire and 219 patients that completed the patient values questionnaire were analyzed. Patients overall report a positive experiences with the general practice they visited. Several gaps were identified in particular in terms of wait times for appointments, general practitioner access to patient medical history, delivery of preventative services, patient involvement in decision-making. Patients with chronic disease report better experience than respondents without a chronic condition, however these patient groups report the same values in terms of qualities of the primary care system that are important to them. Conclusions Data gathered may be used to improve the quality of primary health care services in Greece through an increased focus on patient-centered approaches. Our study has identified several gaps as well as factors within the primary care health system that patient’s perceive as most important which can be used to prioritize quality improvement activities, especially within the austerity period. Study findings may also have application to other countries with similar context and infrastructure.